2022
DOI: 10.1021/acsami.2c12958
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between the 2D “Ligand” and 2D “Host” and Their Assembled Hierarchical Heterostructures for Electromagnetic Wave Absorption

Abstract: Constructing the strong interaction between the matrix and the active centers dominates the design of high-performance electromagnetic wave (EMW) absorption materials. However, the interaction-relevant absorption mechanism is still unclear, and the design of ultrahigh reflection loss (R L < −80 dB) absorbers remains a great challenge. Herein, CoFe-based Prussian blue (PB) nanocubes are coprecipitated on the surface of ultrathin CoAl-LDH nanoplates with the assistance of unsaturated coordination sites. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Previous works on semiconductor metal sulfides in the field of EM wave absorption have focused on MoS 2 , VS 2 , and WS 2 . In the course of our research, we have shown that we can control the morphology of semiconductor Cu 9 S 5 nanomaterials by modulating the growth orientation of its crystals. Compared with previous studies, this work achieves the simultaneous optimization of absorber thickness, bandwidth, and reflection loss by introducing multiple loss mechanisms.…”
Section: Introductionmentioning
confidence: 77%
“…Previous works on semiconductor metal sulfides in the field of EM wave absorption have focused on MoS 2 , VS 2 , and WS 2 . In the course of our research, we have shown that we can control the morphology of semiconductor Cu 9 S 5 nanomaterials by modulating the growth orientation of its crystals. Compared with previous studies, this work achieves the simultaneous optimization of absorber thickness, bandwidth, and reflection loss by introducing multiple loss mechanisms.…”
Section: Introductionmentioning
confidence: 77%
“…In addition, the [Fe(CN) 6 ] 3− in the electrolyte can chelate with the incompletely coordinated Co atom in the FeN 3 -CoN 2 S site on the surface of Co/Fe-SNC800, which can also contribute to the disappearance of the Co 2+ /Co 3+ redox peaks. 61–69…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the [Fe(CN) 6 ] 3À in the electrolyte can chelate with the incompletely coordinated Co atom in the FeN 3 -CoN 2 S site on the surface of Co/Fe-SNC800, which can also contribute to the disappearance of the Co 2+ /Co 3+ redox peaks. [61][62][63][64][65][66][67][68][69] The previous results strongly indicated the electronic coupling between the Co and Fe sites from various aspects, which was further revealed in the microscopy investigations. Thus, the…”
Section: Papermentioning
confidence: 93%
“…[55] It can be observed that the tan 𝛿 𝜖 values of L-MXene and P-Mxene ML are larger than those of the other two samples (N-MXene NRs, P-MXene L) (Figure 4k). For EMW absorption, attenuation constant (𝛼 = [((2) 1/2 𝜋f)/c]/{(μ"𝜖"μ"𝜖") + [(μ"𝜖"μ"𝜖") 2 + (𝜖"μ" + 𝜖"μ") 2 ] 1/2 } 1/2 ), [56] eddy current (C 0 = μ"(μ′) −2 f −-1 = 2𝜋μ 0 d 2 𝜎), and impedance matching (Z = (μ r /𝜖 r ) 1/2 tanh|j2𝜋fd(μ r 𝜖 r ) 1/2 /c|) are important parameters to reveal the EMW absorption mechanism. Among them, 𝛼 represents the EMW attenuation ability.…”
Section: Resultsmentioning
confidence: 99%